Capital markets : Institutions, instruments and risk management - Fabozzi, Frank J. (Cambridge, Massachusetts : The MIT Press, 2015)
Capital Markets covers the instruments, the players, and the principles of valuation, along with describing the wide range of instruments for financing, investing, and controlling risk available in today's financial markets.
Part I. Introduction -- Part II. The players -- Part III. Basics of cash and derivatives markets -- Part IV. Risk and return theories -- Part V. Interest rate determination and debt pricing -- Part VI. Equity markets -- Part VII. Debt markets -- Part VIII> Derivative markets .
Includes index.
Keywords: CAPITAL MARKET